XEN® Gel Stent: A Comprehensive Review on Its Use as a Treatment Option for Refractory Glaucoma - Fea AM (Dove Medical Press, 2020)
Antonio M Fea,1 Georges M Durr,2,3 Paola Marolo,1 Lorenza Malinverni,1 Mario A Economou,4 Ike Ahmed5 1Struttura Complessa Oculistica, Città Della Salute e Della Scienza di Torino, Dipartimento di Scienze Chirurgiche - Università Degli Studi di Torino, Torino, Italy; 2Department of Ophthalmology, Université de Montréal, Montréal, Québec, Canada; 3Department of Ophthalmology, Centre Hospitalier Universitaire de Montréal (CHUM), Montréal, Québec, Canada; 4Karolinska Institute, Stockholm, Sweden; 5Department of Ophthalmology and Vision Sciences, University of Toronto, Toronto, Ontario, CanadaCorrespondence: Antonio M Fea Email antoniomfea@gmail.comAbstract: The XEN Gel Microstent is a subconjunctival microinvasive glaucoma surgical device developed with the aim of improving the predictability and safety profile of bleb-forming glaucoma surgical procedures. The stent is a hydrophilic tube composed of a porcine gel cross-linked with glutaraldehyde with good stability and biocompatibility with minimal tissue reaction. This device has demonstrated promising outcomes with fewer risks compared to traditional surgeries. The aim of the review is to present early studies on different designs of the XEN Gel Stent, to summarize different surgical techniques of implantation and to analyze more comprehensively the results, complications and rates of needling of the commercially available device (Xen 45). The review will address separately special cases (PXG, UVG, ICE, congenital glaucoma) and describe small series and case reports.Keywords: XEN Gel Stent, glaucoma surgery, review, efficacy, safety, needling